Rancang Bangun Sistem Penghitung Jumlah Burung Walet berbasis Internet of Things (IoT) - Samsul Arifin; Wahyu Anggar Wanto; Garry William Dony; Walman Lumbanraja (Jurnal Fisika Unand, 2026)
Swiftlet nest farming is a source of economic income for several regions in Indonesia, including Central Kalimantan. The constraint faced by swiftlet nest farmers is the use of a manual counting system by estimating the number of birds, which has a high error rate. This problem necessitates the design of a swiftlet counting system. This research aims to design and build an appropriate technology-based monitoring system. The technology required is one that can be used to monitor the number of swiftlets entering and leaving the swiftlet house in real time. The method used is the characterization and calibration of infrared sensors, then designing a sensor data design and acquisition system. The NodeMCU ESP8266 measures the number of objects using an infrared sensor displayed through a Liquid Crystal Display (LCD) and Blynk. Data collection was carried out in six trials with variations in the number of objects passed through the sensor. The test results show an average error percentage of 3% and an accuracy value of 97.5% when throwing one object and an error value of 6% and an accuracy value of 94% when throwing one object. The measurement data is displayed on the LCD and sent to the Blynk application via a smartphone for remote monitoring.